The Arco encyclopedia of embroidery stitches - Butler, Anne (Arco Publishing Inc., 1979)
Photographs of nearly 500 embroidery stitches are grouped in families, including couching, stem, fly, and chain stitches, and accompanied by a diagrammatic form of the stitch illustrating the method of working it.